The New Approaches in Mathematical Modeling of Grain Storage - Bhardwaj, Sandeep (Food Science and Agriculture: Research Highlights Vol. 1, 2025)
After reviewing academic and technical literature it was found that traditional approaches are also significantly important for food security. According to this study, farmers are also adopting modern technology like hermetic storage and automated metal bins. The on-farm storage of grain like cover and plinth storage (CAP) technology also considerably improved since its inception as compared to heap storage of grain. After studying the surveys of agricultural extension, it was found that metal bins are maximum used due to their low cost, easy fabrication and use. For Animal feed storage like hay, the old traditional method of heap storage in the open or in go-downs is preferred by farmers. As a matter fact of these methodologies are basically based on traditional or local considerations. In terms of advancement only monitoring of environmental variables like temperature, breakage of grain, moisture etc are monitored in government godowns and research thrust is only for the use of these environment variables for preliminary design and fabrication of bins and silos. This paper emphasis on comprehensive control and maintenance of grain storage structure to monitor the health of grain through modern systems and technology like structural health monitoring(SHM) through piezoelectric energy, and computational fluid dynamics (CFD) to control environmental variables which is fed through the sensors and data loggers in the structure and Numerical methods like finite element method (FEM), boundary element method (BEM), discrete element method (DEM) etc. used for enhanced control and improvement of design of grain storage structures not restricting to bin and silos. This paper also highlights that low-cost underground grain storage is completely ignored by government agencies and communities due to its vulnerability to infestation of pests. This highlights the use of salt caverns if available as the best alternative to underground grain storage structures.